Science and partial truth a unitary approach to models and scientific reasoning - Costa, Newton C. A. da.; French, Steven; Oxford eBooks (Oxford : Oxford University Press, 2003)
Explores the consequences of adopting a 'pragmatic' notion of truth in the philosophy of science. This framework describes issues to do with belief, theory acceptance, and the realism-antirealism debate, as well as the nature of scientific models and their heuristic development.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Reasoning; Science -- Philosophy; Electronic books